Perlindungan Hukum Bagi Kreditur Akibat Jaminan Fidusia Yang Dialihkan Oleh Debitur Kepada Pihak Lain Tanpa Sepengetahuan Kreditur - Muhamad Rayza Aditya; Alisyahbana Saleh (Fakultas Hukum Universitas Gresik, 2023)
The phenomenon that often occurs in society is that fiduciary collateral objects that are physically controlled by the debtor have been transferred to other parties without the creditor's knowledge. Problems are known when the debtor does not carry out his obligations, namely paying installments to creditors. The purpose of this research is to find out the legal consequences of fiduciary guarantees transferred by the debtor to another party without the creditor's knowledge and how the legal protection for creditors is for fiduciary guarantees transferred by the debtor to another party without the creditor's knowledge. The method used in this research is normative juridical research. From the research results it can be obtained that the legal consequences of fiduciary guarantees being transferred to other parties without the creditor's knowledge is the emergence of criminal sanctions for the debtor in accordance with the provisions of Article 46 of Law Number 42 of 1999 concerning Fiduciary Guarantees. Legal protection for creditors against fiduciary guarantees that are transferred by the debtor to another party without the creditor's knowledge, namely in the form of repressive protection. The creditor can sue the debtor for his actions in the district court and the court of law provides legal protection in the form of a court decision in favor of the creditor.